SPORT ACTIVITIES OF URBAN POOR CHILDREN - Serkan GÜZEL (Fırat University, 2019)
Children are significant social actors who shape the institution of family from the point of view of love, entertainment, joy and sharing on one hand; and maintaining lineage on the other hand. As seen, the aim of this study reveals how urban poor families perceive state offering opportunities for urban poor family children from their perspective. In other words, it points out how the state is reflected within urban poor households especially from a societal dimension. In this way, our research universe consists of two hundred and twenty-two school students defined by province police headquarters. Sampling technique has been preferred as it successfully facilitated the whole research process. So, families of twenty-two school students represented within the research sample have been reached. However, it has been tried to reach particularly mothers who are much more concerned about their children within the family. In this sense, deep interview research technique has been preferred as the methodological reason of this study depends upon especially the problematics that research participants may put forth from their perspective. One of the significant findings of this study is first of all that urban poor families appreciate their children as valuable. Another finding is that urban poor families want for their children to take quality education and sports activities, and believe that all of the support within these two fields will come from the state. After all, because of integrating with urban life and the growing importance of urban poor families it has to be taken into account how urban life in which they live offer opportunities to them.